Mobilne aplikacje medyczne jako narzędzia wspierające organizację polskiego systemu ochrony zdrowia - Kajzer, Szymon; Szlachetka, Natalia (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article shows an important role of mobile medical applications as tools that improve the quality and availability of health care. It indicates that these are stabilizing solutions and that they affect positively the effectiveness of the health care system. The motivation for discussing the software is to find the reason for rare usage of the applications during treatment of the beneficiaries. The aim of the analysis was to examine patients’ knowledge of medical applications, arguing that lack of knowledge about health software among medical care recipients may be a key factor in the low interest of the providers. Moreover, it could cause the lack of motivation to take any action. The obtained results allowed us to determine the percentage of people using or not using the application. The analysis has identified the most important barriers and biases toward medical software. In addition, the data provided information on the types of applications most frequently used by the examined and indicated features that could be motivators for potential users to install them
Keywords: mobile applications; medicine; patient; Internet; e-health; telemedicine